MARKETING STRATEGY TO DRIVE IMPULSE BUYING AND HEDONIC SHOPPING ON SHOPEE E-COMMERCE: A NEUROMARKETING-BASED APPROACH - Fanggidae, Ronald; Sanaji, Sanaji; Sulistyowati, Raya; Sumbawati, Novi (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This article explores marketing strategies aimed at increasing impulse buying and hedonic shopping behavior on the e-commerce platform Shopee, using a neuromarketing approach. The article highlights the rapid growth of online shopping in Indonesia, especially among the younger demographic, and uses the Zaltman Metaphor Elicitation Technique (ZMET) to explore consumer perceptions and motivations. Key findings suggest that emotional responses and sensory stimuli significantly influence impulse buying, with factors such as attractive promotions, product variety, and ease of payment playing a significant role. The study offers valuable insights for marketers to develop effective strategies tailored to consumer behavior on Shopee while also acknowledging limitations such as the small sample size and qualitative nature of the study. Keywords: Hedonic Shopping; Impulse Buying; Neuromarketing; Marketing Strategy